2021
DOI: 10.3390/medicina57080788
|View full text |Cite
|
Sign up to set email alerts
|

WNT-5a and SOST Levels in Gingival Crevicular Fluid Depend on the Inflammatory and Osteoclastogenic Activities of Periodontal Tissues

Abstract: Background and Objectives: Wnt signaling leads to stimulation of osteoblasts and it reduces osteoclastogenesis and bone resorption via the regulation of the osteprotegrin and receptor activator of nuclear factor kappa-Β ligan (RANKL). Wnt signaling pathways are regulated by their physiological antagonists such as sclerostin (SOST) as well as WNT-5a. The aim of this study was to determine the total amount of Sclerostin and WNT-5a in the gingival crevicular fluid (GCF) in sites with a continuum from a healthy to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(20 citation statements)
references
References 49 publications
0
20
0
Order By: Relevance
“…Wnt5a is usually at a low expression level in healthy adult tissues compared to those of the embryo ( Yap et al, 2014 ), but the dysregulation of Wnt5a usually results in it being overexpressed, resulting in a number of diseases. It was significantly elevated in gingival crevicular fluid at periodontitis sites when compared to healthy gums ( Chatzopoulos et al, 2021 ). The expression of Wnt5a was upregulated in the inflammatory microenvironment simulated by LPS in vitro ( He et al, 2014 ), which was in agreement with our results.…”
Section: Discussionmentioning
confidence: 99%
“…Wnt5a is usually at a low expression level in healthy adult tissues compared to those of the embryo ( Yap et al, 2014 ), but the dysregulation of Wnt5a usually results in it being overexpressed, resulting in a number of diseases. It was significantly elevated in gingival crevicular fluid at periodontitis sites when compared to healthy gums ( Chatzopoulos et al, 2021 ). The expression of Wnt5a was upregulated in the inflammatory microenvironment simulated by LPS in vitro ( He et al, 2014 ), which was in agreement with our results.…”
Section: Discussionmentioning
confidence: 99%
“…and the Wnt‐5a GCF levels were significantly lower in gingivitis than in periodontitis and healthy sites 50 . No differences were observed in another study 51 . Based on the available data from two studies, no significant correlation between Wnt5a levels and clinical parameters was detected 50,51 …”
Section: Resultsmentioning
confidence: 93%
“…In addition, a fifth study demonstrated that when generalized moderate and severe periodontitis was considered, SOST exhibited significantly higher amounts in the GCF of periodontitis sites 50 . No significant differences between healthy and periodontitis sites were found in only one study 51 . When the correlation between SOST and clinical parameters was evaluated, significant positive findings were identified in five investigations 45,47,48,50,57 .…”
Section: Resultsmentioning
confidence: 94%
See 2 more Smart Citations